Application of SixNy:Hz (SiN) as index matching layer in a-Si:H thin film solar cells - Singh, Chandra Bhal (2014)
The difference in refractive indices of glass substrate and transparent conducting oxide (TCO) electrode causes optical reflection in thin film solar cells, which results in lower absorption of light for devices. An anti-reflection layer between glass and TCO is required to reduce the loss of light due to optical reflection. Silicon nitride (SixNy:Hz) films have shown antireflection property. The refractive index of SixNy:Hz films can be engineered by changing the silicon or nitrogen content in the film. Here, we report the optimization of refractive index of SixNy:Hz to achieve a value between refractive index of glass (1.5) and TCO film (2.0). SixNy:Hz films have been deposited in a RF-plasma enhanced chemical vapour deposition system operating at a frequency of 13.56 MHz. The substrate temperature was fixed at 300 °C. Fourier transform infrared analysis has been used to determine the nature of Si-N, N-H, and Si-H bonding in the films. Refractive index of films has been measured using spectroscopic ellipsometer. The optical reflectance and transmission of SixNy:Hz and SixNy:Hz/TCO layers have been measured using UV/VIS spectrometer. The gas flow rate ratio of N2/SiH4 has been varied from 235 to 470. Decrease in transmittance of SixNy:Hz/TCO layer is observed with increase in silicon concentration in the film. Refractive index of SixNy:Hz also increased with an increase of the silicon content in the films. The reflectance of TCO films has been decreased from 15% to 8% when SixNy:Hz film is incorporated between glass substrate and TCO film. An improvement of around 20% has been observed in current density of solar cells having SixNy:Hz film as refractive index matching layer with refractive index 1.83. Thus, SixNy:Hz film as refractive index matching layer can be used to improve the solar cells device efficiency.